Accuracy of Template Versus Ultrasound Identification of the Reservoir Access Port of Intrathecal Drug Delivery System. Issue 7 (20th December 2019) - Matthys, Camille; Jacobs, Myriam; Rossat, Julien; Perruchoud, Christophe
Abstract : Introduction: Precise localization of the center of the reservoir access port (RAP) of intrathecal pump is a crucial step to ensure a safe refill procedure. In difficult refill cases, ultrasound guidance has been reported useful. Being more expensive and time‐consuming, the purpose of the study was therefore to identify situations in which sonographic localization is more accurate than the template method, in order to restrict its use to these defined conditions. Materials and Methods: The RAP was localized using the template provided by the manufacturer and by ultrasound guidance. The distance between the two points was measured. A distance superior to 3.5 mm, corresponding to the radius of the silicone septum of the RAP, was considered a clinically significant deviation. Results: During the study period, 22 patients underwent a total of 81 refill procedures. No significant correlation was found between the distance between the two points and age, height, weight, body mass index (BMI) or abdominal perimeter. The correlation was significant between distance and pump's depth. According to the ROC curve, the sensitivity of ultrasound identification of the RAP was 69.2% and the specificity 83.3% when the pump was implanted at a depth of 10 mm. Discussion: Our results are comparable to these published in the literature, pointing the usefulness of ultrasound for refill of deeply implanted pumps. Our study provides an additional element by specifying the depth from which the ultrasound seems to be superior to template. Conclusion: Poor accuracy in RAP identification of intrathecal pump can lead to life‐threatening complications. The results of our study suggest that the localization of recessed‐RAP can be improved by ultrasound in cases of pump implanted deeper than 10 mm. For more superficially implanted devices, the template method seems to be as accurate as ultrasound.